Remembering the Holocaust a debate - Alexander, Jeffrey C., 1947-; Jay, Martin, 1944- (New York ; Oxford : Oxford University Press, 2009)
This title brings together a wide range of leading historians social scientists, and literary scholars to explore the controversy surrounding the legacy of the Holocaust.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Holocaust, Jewish (1939-1945) -- History; Holocaust, Jewish (1939-1945), in literature; Holocaust, Jewish (1939-1945), in art; Holocaust (Jewish theology)